PENERAPAN AKUNTANSI DALAM PERSPEKTIF BUDAYA MADURA PADA YAYASAN NURUL HORIYAH - Ana Mariana; Syahril; Miftahol Arifin (Faculty of Islamic Economics and Business, 2023)
Application of accounting is the implementation of activities in collecting and managing transactions. This study aims to determine the culture of Madura in implementing the accounting system at the Nurul Horiyah foundation. This type of research is a qualitative research type using subjective data and document data. Data collection techniques using observation, interview and documentation techniques. From the research results obtained, it can be concluded that the financial reports applied to organizations under the auspices of the Nurul Horiyah foundation in Tobang Village apply the madura culture of Bhupa' Bhabhu' Guru Rato where the accountability of financial statements by respect for the head of the foundation like a parent (bhapa' bhabhu'), respect for Allah SWT in being accountable for reports as a teacher (ghuru), and finally respect for the government (rato). However, reports that are accountable to the government for non-profit organizations are not in accordance with reporting standards based on ISAK 35 which use very simple reports. Keywords : Culture, Madura, Non-Profit Entity, Application of Accounting.